Association between educational level and hypertension with decrease of cognitive function among elderly at Puskesmas Mengwi I - Vijay Ramachandran; Putu Aryani (Intisari Sains Medis, 2018)
Background: One of most emerging disease in elderly is the decreasing of cognitive function. Some factors that could affect cognitive function are sociodemographic factors such as genetics, age, gender, educational level, occupation also some diseases like a cerebrovascular disease, metabolic disease, brain tumor, and head trauma.Methods: The purpose of this research was to understand the association between educational level and hypertension with a decrease of cognitive function in elderly. This research was analytic cross-sectional study. The number of samples that obtained was 41 elderly who met the inclusion criteria. The sample data obtained by filling an MMSE questionnaire to aces cognitive function.Results: In general, 16 from 41 sample (39%) has a decrease in cognitive function. Bivariate analytic with chi-square method showed that there’s a significant relationship between educational level and a decrease of cognitive function (p= 0.001) while also showed that there’s no significant relationship between hypertension and decrease of cognitive function.Conclusion: It can be concluded that there was a significant relationship between educational level and a decrease of cognitive function in elderly but no significant relationship between hypertension and decrease of cognitive function in elderly. The results of this study were expected to be used as a basis for further research in the future.